Analisis Produk Halal Pada Usaha UMKM “Eyang Dimsum” Di Lau Dendang - Tiara Nurul Syahida; Nikira Nikira; Rizqa Amelia (Pusat Riset dan Inovasi Nasional, 2023)
The halalness of a product that is produced is a mandatory requirement for every consumer or use of that product, especially Muslim consumers. In international trade practices, the issue of halal certification and marking of a product has received good reviews in order to provide protection for Muslim consumers around the world as well as a strategy in facing the challenges of globalization. This research method is a qualitative research method with a mini-research approach with interview techniques that aim to find and collect information through sources regarding standing history, experience and other information. The purpose of this research is to see the halalness of a food product produced by Eyang Dimsum producers, related to how the products produced meet sales standards and halal certification.